SOCIAL TRUST IN PUBLIC AUTHORITIES AS A FACTOR OF CIVIL SOCIETY DEVELOPMENT - Palagnyuk, Yuliana (Public Administration and Regional Development, 2021)
The study of the problem of social trust in various social institutions is relevant in modern Ukraine in the conditions of the occupation of Donbass’s part and Crimea, the armed conflict in the east of our country, the deterioration of the socio-economic situation of citizens, ongoing reforms in various fields. Therefore, the aim of the study is to substantiate the relationship between social trust in public authorities and the development of civil society in the context of reforms in various fields in modern Ukraine. The essence of such key concepts as "trust", "social trust" is considered, including in the latest researches of the western scientists. The level of social trust in various social institutions in 2020-2021 is analyzed in accordance with the international monitoring project World Values Survey, as well as Ukrainian sociological centers. It is shown that a low level of social trust, including in public authorities, is a consequence of the negative experience of Ukrainians’ participation in trusting relations with those social institutions. It is emphasized that in recent years in Ukraine there is an increase in social trust, according to the latest sociological research of both international and Ukrainian organizations, to volunteer organizations and to local governments. This is one of the positive aspects of decentralization reform, a testament to the effectiveness of civil society at the level of community development. Thus, a high level of social trust indicates a developed civil society, when citizens through the implementation of the principles of openness, transparency, legality of public administration, cooperation with public authorities, involvement in the process of formation, implementation and evaluation of public policies in various fields act together with public authorities in order to improve the conditions of their lives in the state in general, and in the community in particular.